Biodiesel Production From Jatropha Curcas L. Oil Using Supercritical Methyl Acetate And Methanol Process - Muhammad Niza, Noorzalila (2011)
Biodiesel synthesized from non-edible oil of Jatropha curcas L. (Jatropha) oil offers several advantages compared with edible oil such as it does not compete with food resources. However, Jatropha oil consists of high free fatty acids content, hence, the production of biodiesel through conventional alkaline catalyst may lead to problems with saponification. Furthermore, the application of methanol in transesterification process may result to oversupply of glycerol production as by-product. Therefore, in this study non-catalytic supercritical method using methyl acetate as the solvent was employed in transesterification of Jatropha oil to produce biodiesel.